INITIAL PUBLIC OFFERING (IPO) IN UZBEKISTAN: THEORY, PRACTICE AND LEGAL REGULATION (TSUL LEGAL REPORT, 2026)
The article is aimed at disclosing of the legal nature of Initial public offering as a mechanism for attracting additional funds from joint-stock companies in Uzbekistan. The analyze of this mechanism is based on legal documents, regulating this process and practice in Uzbekistan, theoretical basics and foreign scientists’ attitudes, then the experience of Initial public Offering of such foreign companies as FixPrice and Facebook. Additionally, the article examines in detail the advantages and disadvantages of companies entering the stock exchange and selling their shares to the public through an IPO. Based on the results of the analysis of national legislation and the practice of foreign companies on the Initial Public Offering, we compared the Initial and Secondary public offerings, their legal nature and distinctive features from each other. Also, we found out that the definitions of the concepts of IPO and SPO established by the legislation of the Republic of Uzbekistan are incorrect and therefore they do not coincide with the practice of IPO and SPO of national companies and foreign experience.